Effects of Qihuang Needling on Motor Function for Patients With Parkinson's Disease: Study Protocol for a Multicenter, Randomized Controlled Trial - Yang, Lian-Sheng; Li, Yang-Mei; Zhou, Dan-Feng; Zhao, Bai-Ming; Zheng, Shu-Zhen; Chen, Zhen-Hu; Zhang, Kun; Lu, Li-Ming (Frontiers in Neurology, 2022)
Background: Although significant progress has been made in the pharmacologic management of Parkinson’s Disease (PD), effective management of movement disorders is still a hurdle for therapeutics targeting PD. Acupuncture is one therapeutic option that could potentially improve the motor function of PD and is widely used as adjuvant therapy. Among the various acupuncture approaches, Qihuang Needling (QHN) therapy has been found to improve motor-function control for PD patients. However, evidence regarding its efficacy remains scarce. Therefore, to address this need, this study will determine the effects of QHN therapy on motor function in PD patients and compare it to placebo effects. Methods: This trial is a multicenter, prospective randomized controlled clinical trial. We will randomly allocate 144 participants to two groups of 72 patients. Patients in the treatment group will be treated with QHN therapy. The control group will undergo insertion of acupuncture needles at sham-acupoints not corresponding to acupuncture points. Participants in the verum treatment group and sham-acupuncture control group will receive 9 sessions over six weeks followed by 8 weeks of follow-up. The primary outcome is the change of motor function from baseline to week 6 and week 14 measured by Parkinson’s Disease Rating Scale-Part III Motor Examination. Secondary outcome measures include the change of Parkinson’s Disease Daily Quality of Life-39 and Non-Motor Symptoms Scale for Parkinson’s disease from baseline to week 6 and week 14. Discussion: The results of this trial will generate data to improve our general understanding of the efficacy of QHN therapy on motor function in PD patients and thoroughly compare these responses to the placebo effect. Trial registration: The trial was registered at the Chinese Clinical Trials Registry (ChiCTR- 2000030871) on 16 March 2020.